ARCHITECTURE "PAPER" COMPETITIONS 20-30 YEARS OF THE TWENTIETH CENTURY. AND THEIR IMPACT ON THE FORMATION OF MODERN ARCHITECTURAL IDEAS - , О. М. (Municipal economy of cities. Series: «Economy science», 2013)
Consider the organizational and methodological and software architectural features "paper" competitions and their impact on the innovative theory and practice.